Primary Hyperparathyroidism: An Overview - Jessica MacKenzie-Feder; Sandra Sirrs; Donald Anderson; Jibran Sharif; Aneal Khan (International Journal of Endocrinology)
Primary hyperparathyroidism is a common condition that affects 0.3% of the general population. Primary and tertiary care specialists can encounter patients with primary hyperparathyroidism, and prompt recognition and treatment can greatly reduce morbidity and mortality from this disease. In this paper we will review the basic physiology of calcium homeostasis and then consider genetic associations as well as common etiologies and presentations of primary hyperparathyroidism. We will consider emerging trends in detection and measurement of parathyroid hormone as well as available imaging modalities for the parathyroid glands. Surgical indications and approach will be reviewed as well as medical management of primary hyperparathyroidism with bisphosphonates and calcimimetics.